Nocterra (2021), volume 2 ebook Pedal to the metal. - Snyder, Scott (Nocterra (2021), 2022)
Ten years after the world is plunged into an everlasting night that turns all living creatures into monstrous shades, the only way to survive is to stay close to artificial light. Enter Valentina “Val” Riggs, a skilled ferryman who transports people and goods along deadly unlit roads with her heavily illuminated eighteen wheeler.